Laboratory production of organic-based fertilizer from sago (metroxylon sagu rottb.) waste compost - Petrus Rudut, Auldry Chaddy (2010)
Sago waste (SW) has a potential to cause pollution especially when the waste is discarded into rivers and streams. In order to add value to SW, a study was conducted to produce calcium (Ca) and potassium (K) hydroxide, compost and humic acid (HA) from it. The SW was air-dried and some ground. The ground SW was incinerated at 600 °C. Calcium and potassium hydroxide was extracted by dissolving the ash in distilled water at a ratio of 1:500 (ash : water), equilibrated for 24 hours at 150 rpm using a mechanical shaker and filtered. The ungrounded SW was used for compost production. The study had three treatments which were: T1: SW (80%) + chicken feed (5%) + chicken dung slurry (5%) + molasses (5%) + urea (5%), T2: SW (80%) + chicken feed (10%) + chicken dung slurry (5%) + molasses (5%) and T3: SW (80%) + chicken feed (10%) + chicken dung slurry (5%) + urea (5%). Composting was done for 60 days in a white polystyrene box with a size of - 61.5 cm x 49 cm x 33.5 cm. The composts produced were analyzed for pH, total nitrogen, organic carbon, organic matter, ash, cation exchange capacity (CEC), phosphorus and HA using standard procedures. The hydroxide extracted from ash of SW was used to isolate HA of composted SW. The molarity and pH of the hydroxide were 0.002M and 10 respectively. Calcium (42.88mg kg-1) and potassium (29.51mg kg-1). The hydroxide was able to extract 1.15% of HA from the composted SW. A comparison between the yields of HA extracted from the composted SW using the hydroxide of the SW and that of the analytical grade showed no statistical difference. All three treatments did not reach thermophilic phase. Compost of T2 had high quality (pH, total nitrogen, organic carbon, organic matter, ash, cation exchange capacity (CEC), phosphorus and HA) compared to T1 and T3. The compost characteristics of T1 and T3 were similar. The yield of HA of T2 was also significantly higher compared to those of T1 and T3. The chemical characteristics of HA of the three treatments were within the standard range reported by other researchers. Besides HA, liquid HA and fulvic acid (FA) and humin also been extracted from the compost. The treatments for pot experiment were: control without fertilizer (T1); NPK (4.85 g urea, 4.85 g TSP, 2.5 g KCl) (solid) (T2), 400 mL liquid of FA+HA mixed with 4.85 g of urea and 2.5 g of KCl (T3), liquid HA mixed with 4.85 g of urea and 2.5 g of KCl (T4), 400 mL hydroxide (extracted from ash) mixed with 4.85 g of urea and 2.5 g of KCl + 200 g humin in soil (T5) and 400 mL liquid of FA+HA mixed with 4.85 g of urea and 2.5 g of KCl + 100 g humin in soil (T6). Treatments which had humin (T5 and T6) had the highest total dry weight and nutrient use efficiency. SW can be efficiently utilized by producing valuable products such as compost, Ca-K hydroxide as well as organic based fertilizers for agriculture. Furthermore, future investigation on the effect of soil physical properties on nutrient use efficiency is encouraged to seek more understanding on soil-fertilizer and plant interaction.